A utilização do cálculo diferencial e integral para estender os cálculos de áreas de figuras planas e comprimentos de curvas no plano - Oliveira, Gleidson José Dumont (2013)
In this work we will make a brief study on the calculation of areas and lengths highlighting how these can be presented in high school, then we will use the di erential and integral calculus to extend the calculations of areas and lengths. Therefore, this study some of the developments in the history of calculus concepts and their "basic", beyond the definitions of areas, lengths, and applications of limit, derivative and integral. We emphasize that the provision contained in this learning material is not in a single textbook adopted in schools.